Stem cell based therapy retards the progression of osteoarthritis and promotes repair of meniscus injury of sheep model knee joint - Alfaqeh, Hamoud Hussein Mohammed; Mohamad Yahaya, Norhamdan; Chen, Hui Cheng; Chua, Kienhui; Saim, Aminuddin; Haji Idrus, Ruszymah (2010)
ABSTRACT